Likuiditas, Solvabilitas, dan Nilai Perusahaan Subsektor Food and Beverage: Peran Ukuran Perusahaan sebagai Variabel Moderasi - Dinil Islamiyah Assa'adah; Amir Amir; Suryo Budi Santoso; Rezky Pramurindra (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to examine the effect of liquidity and solvency on firm value, with firm size serving as a moderating variable, in food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The study employs secondary data obtained from annual financial statements selected using a purposive sampling technique, resulting in 328 observations. The data were analyzed using panel data regression with the Fixed Effect Model (FEM), selected based on the Chow and Hausman tests. The moderating effect was examined using Moderated Regression Analysis (MRA), while heteroscedasticity and autocorrelation issues were addressed using robust standard errors. The results indicate that liquidity has no significant effect on firm value, whereas solvency has a positive effect on firm value. Furthermore, firm size is unable to moderate the relationship between liquidity and firm value. In contrast, firm size significantly moderates the relationship between solvency and firm value with a negative direction, indicating that firm size weakens the positive effect of solvency on firm value. These findings suggest that investors in the food and beverage subsector place greater emphasis on capital structure than on liquidity when evaluating firm value. This study provides empirical evidence regarding the role of firm size in the relationship between financial ratios and firm value during the post-pandemic period.